Full-length transcriptome atlas of gallbladder cancer reveals trastuzumab resistance conferred by ERBB2 alternative splicing - Ziyi Wang; Li Gao; Ziheng Jia; Liguo Liu; Ao Gu; Zhaonan Liu; Qin Zhu; Yichen Zuo; Mingjie Yang; Shijia Wang; Jiyao Ma; Jingyun Zhang; et al. (Signal Transduction and Targeted Therapy)
Abstract Aberrant RNA alternative splicing in cancer generates varied novel isoforms and protein variants that facilitate cancer progression. Here, we employed the advanced long-read full-length transcriptome sequencing on gallbladder normal tissues, tumors, and cell lines to establish a comprehensive full-length gallbladder transcriptomic atlas. It is of note that receptor tyrosine kinases were one of the most dynamic components with highly variable transcript, with Erb-B2 receptor tyrosine kinase 2 (ERBB2) as a prime representative. A novel transcript, designated ERBB2 i14e, was identified for encoding a novel functional protein, and its protein expression was elevated in gallbladder cancer and strongly associated with worse prognosis. With the regulation of splicing factors ESRP1/2, ERBB2 i14e was alternatively spliced from intron 14 and the encoded i14e peptide was proved to facilitate the interaction with ERBB3 and downstream signaling activation of AKT. ERBB2 i14e was inducible and its expression attenuated anti-ERBB2 treatment efficacy in tumor xenografts. Further studies with patient derived xenografts models validated that ERBB2 i14e blockage with antisense oligonucleotide enhanced the tumor sensitivity to trastuzumab and its drug conjugates. Overall, this study provides a gallbladder specific long-read transcriptome profile and discovers a novel mechanism of trastuzumab resistance, thus ultimately devising strategies to improve trastuzumab therapy.